Analisis Validitas Media Berbasis Curipod dan Perangkat Pembelajaran Materi Proses Termodinamika Kelas XI di SMA Negeri 1 Sunawa - Nidar Mawati Gulo; Trisnawaty Junus Buhungo; Lukman Samatowa (Mataram University, 2026)
Learning physics on the topic of thermodynamic processes requires media and learning tools that match the characteristics of the material in order to support the learning process. Therefore, Curipod-based media and learning tools that are developed need to be validated to ensure their feasibility before being implemented in learning. This study aimed to determine the validity of interactive learning media based on the Curipod platform and learning devices on thermodynamic processes material. Curipod was developed as an alternative interactive learning medium to support physics learning. The selection of this material was based on the abstract nature of physics concepts, which require dynamic visualization to facilitate understanding. This study employed a Research and Development (R&D) approach using the comprehensive ADDIE model, with the research limited to the Development stage. Data were collected through validation sheets assessed directly by experts from the Department of Physics, Faculty of Mathematics and Natural Sciences, Universitas Negeri Gorontalo. The validation process covered four main aspects: content appropriateness, technical presentation, language suitability, and instrument readability. The results showed that the Curipod-based media obtained an average score of 3.77, while the module, teaching materials, student worksheets, learning achievement test, learning implementation observation sheet, student activity observation sheet, and student response questionnaire obtained average scores of 3.80, 3.91, 3.86, 3.85, 3.93, 4.00, and 4.00, respectively. These findings indicate that the developed media and learning devices are categorized as highly valid and can be used in physics learning on thermodynamic processes.